SISTEM PENGUPAHAN TERHADAP BURUH DI UD. BUMI RAHAYU PERSPEKTIF SIYASAH SYAR’IYYAH - Ronaldo, Ryan Rahman; Rahmiati, Rahmiati; Risal, M. Chaerul (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
The current minimum wage determination policy still has obstacles as a result of the unmet uniformity of wages, so the wage mechanism always causes pros and cons between workers and employers / employers. This article seeks to answer the wage mechanism in accordance with the provisions of laws and regulations, especially wages in UD. Bumi Rahayu Polewali Mandar Regency. This type of research uses qualitative research with juridical, sociological and syar'i approaches. Data sources are primary data and secondary data. The results showed that wage provisions have been carried out in accordance with applicable rules, such as a decent income, minimum wage, and things that can be taken into account with wages. As for the implementation of the wage system in UD. Bumi Rahayu uses a wage system based on units of results. The wage mechanism carried out by UD. Bumi Rahayu has been in accordance with the wage system in the concept of siyasah syar'iyyah.